Korelasi Efikasi Diri (Self Efficacy) dan Iklim Sekolah Terhadap Hasil Belajar Siswa Mata Pelajaran Teknologi Informasi dan Komunikasi (TIK) di SMP Negeri 1 Tabanan pada Semester Ganjil Tahun Ajaran 2013/2014 - I Putu Dika Prasetya; Nyoman Sugihartini; I Ketut Resika Arthana; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
This study aimed to determine (1) the correlation between self efficacy towards the learning achievement of Information and Communication Technologies (ICT), (2) the correlation between school climate towards the learning achievement of ICT, and (3) the correlation between self efficacy and school climate jointly towards the learning achievement of ICT. This was an expost-facto research by using correlation technique, which consisted of two independent variables and one dependent variable. The population in this research was all students at SMP Negeri 1 Tabanan with total amount of 550 people. The samples in this research were 232 people. The data for self efficacy and school climate were collected through questionnaires. Meanwhile, ICT learning achievement data was obtained through the ICT daily test mark of students at SMP Negeri 1 Tabanan in odd semester in academic year 2013/2014. The collected data were analyzed parametric statistically by using prerequisite normality test, linearity and regression towards significance. The result of the research shows that: (1) self efficacy does not have any positive and significant correlation towards learning achievement of ICT by 0.125 categorized as very low, (2) school climate does not have any positive and significant correlation towards learning achievement of ICT by -0.144  categorized as very low and (3) self efficacy and school climate jointly have positive and significant correlation towards learning achievement of ICT by 0.230 categorized as low with contribution of 5.27%.